Case reportContact urticaria syndrome caused by haptens: a case report - Gomułka, Krzysztof; Panaszek, Bernard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
In the group of urticaria, contact urticaria syndrome is a particular variety. In these patients, appearance of typical skin lesions is preceded by contact of the skin and mucous membranes with various inhaled allergens, nutrients or contact details. Furthermore, symptoms connected with contact urticaria syndrome are characterized by gradual, stepwise waveform, which can be easily generalized – patients may develop systemic symptoms similar to those found in the angioedema, asthma or anaphylactic shock. It is an attribute of contact urticaria syndrome in the course of which potentially life-threatening symptoms may develop after contact of the skin with the allergen. The underlying mechanisms are poorly understood; both immunological and non-immunological mechanisms are taken into account, therefore contact urticaria syndrome can be classified into two categories – allergic and non-allergic. An intriguing phenomenon seems to be the immediate reaction after exposure to low molecular weight allergens – haptens, such as metals, which are usually the cause of delayed allergic reactions. Diagnosis is based on clinical presentation indicating a coincidence of the onset of allergy with contract with allergen, and helpful exposure tests. Treatment consists of supportive antihistamines and corticosteroids – locally and systemically. In the case of anaphylaxis, appropriate treatment intensification of the integration of pressor amines and hydration is necessary. It is also regarded that prevention is advisable, which consists of relevant information to avoid situations connected with contact with well-known factors. In this paper we describe a case of a 57-year-old female admitted to the Department of Internal Medicine, Geriatrics and Allergology, Medical University in Wroclaw to undergo diagnostic tests of chronic urticaria and angioedema. According to information obtained from the clinical presentation and after the diagnostic procedures, contact urticaria syndrome due to exposure to metals was diagnosed.